2014
DOI: 10.1111/boc.201400038
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in cardiovascular connexin genes

Abstract: Connexins (Cxs) form a family of transmembrane proteins comprising 21 members in humans. Cxs differ in their expression patterns, biophysical properties and ability to combine into homomeric or heteromeric gap junction channels between neighbouring cells. The permeation of ions and small metabolites through gap junction channels or hemichannels confers a crucial role to these proteins in intercellular communication and in maintaining tissue homeostasis. Among others, Cx37, Cx40, Cx43, Cx45 and Cx47 are found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 188 publications
(243 reference statements)
0
29
0
2
Order By: Relevance
“…In the heart atrial fibrillation may result from mutations in Cx40 (Molica et al, 2014). Cxs also play prominent roles in acquired diseases.…”
Section: General Introduction To Connexinsmentioning
confidence: 99%
“…In the heart atrial fibrillation may result from mutations in Cx40 (Molica et al, 2014). Cxs also play prominent roles in acquired diseases.…”
Section: General Introduction To Connexinsmentioning
confidence: 99%
“…Gap junction proteins form channels between neighboring cells to allow direct intercellular exchanges of ions and small metabolites, which are needed to coordinate vasoconstriction and vasodilation along the vessels. 38,39 Genetic studies show that mice lacking Cx40 develop hypertension because of increased secretion of renin and reduced relaxation of peripheral vessels. 40 These defects have recently been shown to be at least partially dependent on endothelial Cx40 function indicating that Cx40 expression levels regulate blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…19 Genetic polymorphisms have been detected in both promoter regions of GJA5 and suspected to be associated with risk of cardiovascular diseases, including hypertension. 39 These polymorphisms have been shown to affect GJA5 promoter activity by reducing gene expression by approximately half with interassay variations ranging from 20% to 65% reduction. By comparing the expression levels of Cx40 in sections of human skin biopsies isolated from 5 healthy donors and 4 patients with HHT2, we have confirmed that important differences exist between individuals, and more importantly, we reveal that Cx40 protein levels are particularly low in the majority of a small selection of patients with HHT2 compared with the healthy donors supporting an association between ALK1 signaling and Cx40 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cxs are members of a family of proteins encoded by 20 to 21 different mammalian genes, which are expressed in a large variety of tissues [89,90]. Cx genes are classified according to sequence homology and are divided into five subfamilies [91]; cardiovascular Cxs belong mostly to the α subfamily ( GJA ).…”
Section: Connexins and Pannexinsmentioning
confidence: 99%